Transcriptome Analyses of the Anti-Proliferative Effects of 20(S)-Ginsenoside Rh2 on HepG2 Cells - Zhang, Ji; Li, Weibo; Yuan, Qiaoyun; Zhou, Jing; Zhang, Jianmei; Cao, Yufeng; Fu, Guangbo; Hu, Weicheng (Frontiers in Pharmacology, 2019)
20(S)-ginsenoside Rh2 (Rh2), a well-known protopanaxadiol-type ginsenoside from Panax ginseng has especially gained attention for its anticancer activities on various types of human cancer cells. However, the molecular mechanism through which Rh2 promotes apoptosis in hepatocellular carcinoma (HePG2) cells is not known at the transcriptome level. Rh2 can specifically inhibit the proliferation of HePG2 in a dose- and time-dependent manner. Moreover, Rh2 can significantly increase the apoptosis which was related with an increase in protein expression levels of caspase-3, caspase-6, and poly (ADP-ribose) polymerase. Comparison of RNA-seq transcriptome profiles from control group and Rh2-treated group yielded a list of 2116 genes whose expression was significantly affected, which includes 971 up-regulated genes and 1145 down-regulated genes. The differentially expressed genes in p53 signaling pathway and DNA replication may have closely relationships to the cells apoptosis caused by Rh2 treatment. The results of qPCR validation showed that dynamic changes in mRNA, such as CDKN1A, CCND2, PMAIP1, GTSE1, and TP73.